Hemipilia basifoliata (Orchidaceae) – an addition to the orchid flora of India - Chowlu, Krishna; Tsering, Jambey; Nageswarao Rao, Abbareddy; Kabeer, K. Ahmed; Ray, Ajit (Biodiversity: Research and Conservation, 2025)
The rare temperate orchid Hemipilia basifoliata (Finet) Y.Tang & H.Peng is reported here as a new species in the flora of India from Lower Dibang Valley District in the state of Arunachal Pradesh (north-eastern India). This small-sized orchid was found growing at 2400 m asl (28°14ꞌ7ꞌꞌN, 95°53ꞌ55ꞌꞌE) in June 2024. Its morphological description as well as photographs of plant habit and dissected floral parts are provided.